Track geotechnology and substructure management - Selig, E. T. 1933- (Thomas Telford, 1994)
This volume is a comprehensive study which provides practical advice and guidance on the important role played by ground engineering in the construction of railway track, the use of which will result in optimum quality with the minimum maintenance effort and the most economical use of resources.